Imaging Modalities for the Noninvasive Assessment of Fibrosis in Crohn's Disease - Cristina Stasi; Massimo Falchini; Stefano Milani (The Scientific World Journal)
The development of strictures in Crohn's disease is a main cause of hospitalization and often represent an indication for surgery. The differentiation between inflammatory and fibrotic strictures is useful to determine the optimal treatment. Today, the availability of noninvasive methods to assess the presence and extension of strictures offers new tools for the diagnosis and follow-up of the disease. Bowel ultrasound, power doppler ultrasound, contrast-enhanced ultrasound, magnetic resonance imaging offer the additional advantage that they do not expose patients to ionizing radiation. In this paper we provide an update on the accuracy of these noninvasive methods for the diagnosis of Crohn's disease.